The THE EFFECT OF EMOTIONAL INTELLIGENCE BASED ON GENDER ON THE LEVEL OF ACCEPTANCE IN INTRODUCTION TO ACCOUNTING IN STIE PEMUDA - Setyowati, Lisa (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to determine the effect of gender based emotional intelligence on the level of understanding of introductory accounting for STIE Pemuda students. The variables used in this study were emotional intelligence as the independent variable, the level of understanding of introductory accounting as the dependent variable and gender as a dummy variable. This research is a quantitative research with data analysis techniques used, namely the t test and F test. The source of data in this study is primary data, namely the questionnaire method distributed via google form at STIE Pemuda. The population in this study were students of STIE Pemuda class 2019 with the number of samples processed, namely 46 people. The results of this study are based on the results of the T test of emotional intelligence variables obtained a significance value of 0.061. Emotional intelligence has a p-value <alpha (1%), which means that the emotional intelligence variable has a partial effect on the level of understanding of introductory accounting. Then for the gender dummy variable, it can be concluded that the gender dummy variable has a value of 0.219> 0.1, which means that gender does not affect the level of accounting understanding or in other words there is no difference in accounting understanding between male students and female students. Based on the results of the F test, it can be seen that the significance level shows a value of 0.065 <0.1 so that it can be concluded that emotional intelligence (X) has a simultaneous effect on the level of understanding introductory accounting (Y).